The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/10428191003754608
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system complications during treatment of acute lymphoblastic leukemia in a single pediatric institution

Abstract: Central nervous system (CNS) complications during treatment of childhood acute lymphoblastic leukemia (ALL) remain a challenging clinical problem. Outcome improvement with more intensive chemotherapy has significantly increased the incidence and severity of adverse events. This study analyzed the incidence of neurological complications during ALL treatment in a single pediatric institution, focusing on clinical, radiological, and electrophysiological findings. Exclusion criteria included CNS leukemic infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 13 publications
10
82
2
Order By: Relevance
“…During chemotherapy for ALL, various types of anticancer drugs are administered, and it is difficult to identify which drug induces PRES. Actually, in a review of PRES during chemotherapy for childhood ALL, the onset of PRES could not be related to one specific drug because it occurred during different phases of the protocol (induction, consolidation, reinduction, and maintenance) [12]. However, Panis et al [8] reported that the incidence of PRES increased after revision of the protocol, which increased L-asparaginase administration.…”
Section: Discussionmentioning
confidence: 97%
“…During chemotherapy for ALL, various types of anticancer drugs are administered, and it is difficult to identify which drug induces PRES. Actually, in a review of PRES during chemotherapy for childhood ALL, the onset of PRES could not be related to one specific drug because it occurred during different phases of the protocol (induction, consolidation, reinduction, and maintenance) [12]. However, Panis et al [8] reported that the incidence of PRES increased after revision of the protocol, which increased L-asparaginase administration.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a high frequency of acute CNS complications were reported by Parasole et al as 33% over a 9-year period during the maintenance treatment of AIEOP-BFM-ALL-2000 protocol which also administered intensive intrathecal therapy during maintenance. 7 The development of acute central neurotoxicity in literature is strongly correlated with intensive triple intrathecal administration and a combination of high-dose intravenous methotrexate with triple intrathecal therapy. 4,7,8,10 In contrast to the findings of BFM-based AEIOP-ALL studies, no acute CNS complication was observed during maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The reported neurotoxicity incidence ranges from 3% to 18.4% in various studies. [3][4][5][6][7][8] These studies usually included peripheral neuropathy, cranial irradiation, CNS leukemic infiltration, long-term neurocognitive defects, and posttreatment late-onset encephalopathy. However, in our series, only the factors causing an acute central neurological event during intensive chemotherapy were considered and their long-term outcomes were discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive chemotherapy was also identified as a risk factor in two young patients with ALL who developed PRES following acute renal failure, hypertension and seizures during GRALL-2005 induction chemotherapy [10]. A 9-year retrospective analysis of central nervous system (CNS) complications in patients with ALL in a single Italian pediatric institution found PRES being the most frequent neurological complication following treatment with the AIEOP-BFM-ALL-2000 protocol [11]. PRES also occurred in two patients with ALL following multidrug induction chemotherapy with vincristine, daunomycin, prednisone, Lasparaginase and intrathecal methotrexate [12], where the second patient also developed tumor lysis syndrome immediately after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%